An Adaptive Hybrid Vertical Equilibrium/Full‐Dimensional Model for Compositional Multiphase Flow. Issue 1 (21st January 2022) - Becker, Beatrix; Guo, Bo; Buntic, Ivan; Flemisch, Bernd; Helmig, Rainer
Abstract: Efficient compositional models are required to simulate underground gas storage in porous formations where, for example, gas quality (such as purity) and loss of gas due to dissolution are of interest. We first extend the concept of vertical equilibrium (VE) to compositional flow, and derive a compositional VE model by vertical integration. Second, we present a hybrid model that couples the efficient compositional VE model to a compositional full‐dimensional model. Subdomains, where the compositional VE model is valid, are identified during simulation based on a VE criterion that compares the vertical profiles of relative permeability at equilibrium to the ones simulated by the full‐dimensional model. We demonstrate the applicability of the hybrid model by simulating hydrogen storage in a radially symmetric, heterogeneous porous aquifer. The hybrid model shows excellent adaptivity over space and time for different permeability values in the heterogeneous region, and compares well to the full‐dimensional model while being computationally efficient, resulting in a runtime of roughly one‐third of the full‐dimensional model. Based on the results, we assume that for larger simulation scales, the efficiency of this new model will increase even more. Key Points: A compositional vertical equilibrium model is coupled to its full‐dimensional counterpart A criterion is developed to adaptively identify and assign regions where the vertical equilibrium model is applicable during simulation A test case of hydrogen storage in a heterogeneous porous aquifer demonstrates efficiency and accuracy of the hybrid model